The Impact of Public Funding to Private R&D: Evidence from Spain (Sociología y tecnociencia, 2024)
The paper analyses the effects of public subsidies to private R&D in Spain. We carried out an evaluation assessment of the program aid of the Centre for the Development for Industrial Technology (CDTI) from 2015 to 2020. CDTI is the main public agency in Spain that grants public support for firms to carry out R&D projects. We combine information on public grants from CDTI with the Technological Innovation Panel (PITEC) that integrates information from the survey on innovation and R&D activities of companies (Innovation Survey). The sample is an unbalanced panel containing 57,988 observations of which 9,116 (16%) correspond to beneficiary companies. We use a mixed approach of Differences-in-Differences with propensity score matching (DD-PSM) in the common support to control for some of the biases that occur when analysing causal effects. We find that public support has positive effects on firms’ R&D resources (i.e. internal R&D investment and job creation) - input additionality- and cooperation -behavioural additionality. However, the impact of public support on firms’ technological outputs varies importantly across sectors, having a positive effect limited to traditional-oriented sectors.
Keywords: Impact assessment; public subsidies; business R&D; innovation; policy evaluation